Taxonomic and phylogenetic appraisal of a new holomorphic Neophyllachora species from Chiang Mai, Thailand - Literatus, Irish C. E.; Maharachchikumbura, Sajeewa S. N.; Withee, Patchareeya; Haituk, Sukanya; Tamakaew, Nisachon; Nguanhom, Jeerapa; Monkhung, Sararat; Thiyagaraja, Vinodhini; Cheewangkoon, Ratchadawan (Phytotaxa, 2023)
Tar spot is a common fungal disease often caused by Phyllachoraceae species, mostly on leaves and also on stems and fruits of a variety of host plant families. We identified a Neophyllachora species from Ficus religiosa leaves in Chiang Mai, Thailand. Phylogenetic analyses using maximum-likelihood (ML) and Bayesian inference (BI) showed the taxonomic placement of our taxon within Neophyllachora. The newly obtained sequences recovered as a sister and distinct clade to Neophyllachora fici with high bootstrap support. Our collection mainly differs from N. fici in having septate paraphyses, hyaline to olivaceous ascospores with 1-2 guttules, and mucilaginous sheath. A holomorphic fungus, Neophyllachora religiosa sp. nov. is introduced here based on the evidence from morpho-molecular analyses. The genus and the species are also identified as the first geographical record to Thailand and the first host record to Ficus religiosa. The synopsis table for the existing species of Neophyllachora and the key to the genus is provided.